Strain-strengthened steel fiber, ultra-high strength and toughness light UHPC material and preparation method of ultra-high strength and toughness light UHPC material
By using technical means such as strain-reinforced steel fibers and modified composite mineral blends in UHPC, the problems of high brittleness and density under high strain conditions are solved, and the high strength, toughness and lightweight properties of the material are improved.
Patent Information
- Application Number
- CN202411927585.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The existing ultra-high performance concrete (UHPC) is highly brittle under high strain conditions, prone to cracks, and has high density, which limits its application in lightweight design.
Strain-reinforced steel fibers are used to significantly improve the mechanical properties and interface bonding force of steel fibers through the Ti-Mg alloy core, carbon nanotube composite coating and laser etching technology. At the same time, the modified composite mineral blend and composite nanoreinforced materials work together to optimize the matrix performance of UHPC.
It significantly improves the tensile strength, toughness and lightweight properties of UHPC, overcomes the brittleness problem of traditional steel fibers under high strain conditions, and achieves the unity of high strength and low density of the material.
Smart Images

Figure BDA0005209586410000141 
Figure BDA0005209586410000151
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of building materials and engineering technology, and specifically relates to a strain-strengthened steel fiber and an ultra-high-strength and lightweight UHPC material and a preparation method thereof. Background Art
[0002] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material that combines high strength, high toughness and high durability. The compressive strength of UHPC can usually reach 150-200MPa, the tensile strength can exceed 10MPa, and it has extremely high crack resistance and compactness, making it widely used in bridges, buildings, marine engineering and protective engineering. Compared with traditional concrete, UHPC not only has significant mechanical performance advantages, but also has outstanding performance in durability and structural stability. However, UHPC still faces many challenges in practical applications.
[0003] First, although UHPC has high strength, it is brittle and prone to cracks that expand rapidly when subjected to stress, eventually leading to brittle failure of the material. This problem significantly reduces the toughness and safety of UHPC, limiting its application in projects that require high energy absorption. In addition, UHPC has a high density, usually 2.4-2.6g / cm 3 This is because its formula contains a large amount of high-density materials (such as quartz sand and steel fiber), which not only increases the deadweight of the structure, but also limits the widespread application of UHPC under the demand for lightweight design.
[0004] In order to improve the performance of UHPC, the existing technology mainly improves its crack resistance and toughness by adding steel fibers or polymer fibers. However, there are still significant problems with traditional steel fibers as reinforcing materials. First, the surface of steel fibers is smooth, and the bonding force with the matrix interface is weak. It is easy to pull out under stress conditions and cannot fully exert its reinforcement effect. In addition, the distribution of steel fibers in the matrix is usually uneven, and they are prone to agglomeration, resulting in local stress concentration, which weakens the overall performance of the material. More importantly, ordinary steel fibers have poor plastic deformation ability under high strain conditions and cannot effectively achieve strain hardening, which limits the toughening effect of the material. Although some studies have used steel fibers with surface etching or coating treatment to improve interface properties, the improvement effect is limited and the processing cost is high.
[0005] In addition, the use of mineral admixtures and nanomaterials in the existing technology is also insufficient. Traditional UHPC formulations usually only use a single mineral admixture (such as silica fume or fly ash) to improve the matrix performance, and fail to fully utilize the synergistic effect of different mineral materials. Although the introduction of a single nanomaterial (such as nano-silica or carbon nanotubes) can improve the strength and density of UHPC, the reinforcement effect of a single component is limited, and multi-scale reinforcement cannot be achieved. In addition, although the use of lightweight fillers can effectively reduce the density of the material, it often leads to reduced strength and toughness, making it difficult to achieve the unity of high strength and low density.
[0006] Therefore, it is urgent to develop a new type of UHPC that comprehensively solves the above problems, and improves the strength, toughness and lightweight performance of the material through multi-component collaborative design and material compound optimization. Summary of the invention
[0007] The purpose of the present invention is to provide a strain-strengthened steel fiber and an ultra-high-toughness and lightweight UHPC material and a preparation method. The present invention significantly improves the interface bonding force and reinforcement effect of the steel fiber through composite material design and advanced preparation technology, and improves the mechanical properties and lightweight level of UHPC.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] The first aspect of the present invention provides a method for preparing a strain-hardened steel fiber, comprising the following steps:
[0010] (1) Preparation of core alloy
[0011] 80-90 parts by weight of titanium powder and 10-20 parts by weight of magnesium powder are mixed, placed in a vacuum melting furnace, evacuated to 0.01-0.05 Pa, introduced with argon gas, heated to 1550-1650° C., and kept warm for 0.5-2 hours to obtain Ti-Mg alloy, and then Ti-Mg alloy steel wire is prepared by continuous wire drawing process;
[0012] (2) Surface coating treatment
[0013] Three carbon nanotubes with different particle sizes are mixed to obtain mixed carbon nanotubes, 1-2 parts by weight of the mixed carbon nanotubes are added to 10 parts by weight of a 5-10wt% polyvinyl alcohol (PVA) aqueous solution to obtain a suspension, Ti-Mg alloy steel wire is immersed in the suspension, and the carbon nanotubes are coated on the surface of the Ti-Mg alloy steel wire by ultrasonic treatment, and after coating, the carbon nanotubes are vacuum dried at 100-140° C. for 2-5 hours, and then placed in an argon environment at 450-550° C. for thermal curing for 0.5-2 hours to form a dense composite layer to obtain a steel fiber;
[0014] (3) Surface laser etching
[0015] The surface of the steel fiber is processed using a femtosecond laser etching device to obtain the strain-strengthened steel fiber.
[0016] Furthermore, the diameter of the Ti-Mg alloy steel wire in step (1) is 50-150 μm; the three carbon nanotubes with different particle sizes in step (2) are: small-particle carbon nanotubes with a diameter of 5-10 nm and a length of 2-10 μm, medium-particle carbon nanotubes with a diameter of 10-30 nm and a length of 5-20 μm, and large-particle carbon nanotubes with a diameter of 30-50 nm and a length of 10-30 μm, and the mass ratio of the small, medium and large carbon nanotubes with different particle sizes is (4-6):
[0017] (2.5-3.5):(1.5-2.5).
[0018] Furthermore, in step (3), the laser parameters are set as follows: pulse width: 150-300 fs, frequency: 80-120 kHz, laser power: 1.5-3 W, scanning speed: 80-150 mm / s, etching depth: 50-300 nm.
[0019] The second aspect of the present invention provides strain-hardened steel fibers prepared by the above preparation method.
[0020] The present invention attempts to improve the strength and toughness of UHPC materials by using steel fibers, but the inventors found that the effect of ordinary steel fibers is limited, and the bonding force with the matrix interface is weak, and it is easy to pull out under stress conditions. Therefore, the inventors innovatively proposed a new strain-hardened steel fiber. The strain-hardened steel fiber uses Ti-Mg alloy, and through reasonable proportioning and precise smelting process, an alloy steel wire with high strength and high ductility is prepared, which significantly improves the mechanical properties of the steel fiber. Compared with traditional low-carbon steel or stainless steel fibers, Ti-Mg alloy steel wire is lighter and has higher specific strength. The present invention enhances the surface properties of steel fibers through a carbon nanotube-polyvinyl alcohol (CNT-PVA) composite coating, uses three carbon nanotubes with different particle sizes, and uses carbon nanotubes of different sizes to further improve the density of the coating and the multi-scale enhancement effect. Among them, small-particle carbon nanotubes can fill the microscopic pores on the surface of steel fibers and provide better density; medium-particle carbon nanotubes can optimize the mechanical properties of the composite coating and enhance the bonding effect with the matrix; large-particle carbon nanotubes can provide stronger rigid support and enhance the crack propagation damping effect. The compounding of three particle size carbon nanotubes forms a multi-scale distributed reinforcement structure, which makes the coating have higher strength and toughness, and significantly improves the interface bonding performance and reinforcement effect of steel fibers. Regular nano-scale concave-convex textures are formed on the surface of steel fibers by laser etching. This texture structure improves the mechanical locking effect between steel fibers and the matrix, greatly improves the interface bonding force and tensile strength, and overcomes the disadvantage of easy pull-out of traditional smooth steel fibers. The strain-strengthened steel fiber of the present invention achieves higher tensile strength and interface bonding force while being lightweight, providing a more efficient and reliable reinforcement effect for ultra-high performance concrete.
[0021] The third aspect of the present invention provides an ultra-high strength and lightweight UHPC material, which comprises the following components by weight: 40-50 parts of silicate cement, 20-30 parts of modified composite mineral admixture, 15-25 parts of quartz sand, 5-15 parts of lightweight filler, 3-6 parts of composite nano-reinforced material, 1-1.5 parts of high-efficiency water reducer, 0.3-0.7 parts of nano-dispersant, 0.8-1.7 parts of strain-strengthened steel fiber, and 10-15 parts of water.
[0022] Furthermore, the preparation method of the modified composite mineral admixture comprises the following steps:
[0023] (i) mixing silica fume, fly ash and metakaolin in a mass ratio of 4-5:2-3:2-3 to obtain a composite mineral admixture;
[0024] (ii) spraying a silane coupling agent aqueous solution, a sodium metasilicate aqueous solution and a zirconium phosphate aqueous solution into the composite mineral admixture in sequence, drying the admixture after the spraying is completed, and then activating the admixture at 450-550° C. for 0.5-1.5 hours to obtain a modified admixture;
[0025] (iii) The modified admixture is crushed to control the particle size D50≤5 μm, thereby obtaining the modified composite mineral admixture.
[0026] Furthermore, the mass of the silane coupling agent is 0.5-1% of the composite mineral admixture, the mass of the sodium metasilicate is 1-2% of the composite mineral admixture, and the mass of the zirconium phosphate is 0.5-1% of the composite mineral admixture.
[0027] The present invention attempts to improve the mechanical properties of UHPC materials by using silica fume, fly ash and metakaolin in a specific ratio. However, the present invention finds that simply mixing silica fume, fly ash and metakaolin and adding them to the formula easily leads to poor interface bonding with steel fibers. Therefore, the present invention modifies the composite mineral admixture. The modified composite mineral admixture forms a strong interface bond with the carbon nanotube coating of the steel fiber through chemical modification, particle size regulation and surface activity enhancement. In terms of chemical bonding, the silane coupling agent cross-links with the carbon nanotube coating through organic groups, sodium metasilicate improves the active adsorption performance of the interface, and zirconium phosphate forms a stable surface film, further enhancing the durability and corrosion resistance of the interface. In terms of physical filling, the modified composite mineral admixture fills the micropores of the matrix and optimizes the density of the interface transition zone around the steel fiber. At the same time, the compounding of three types of carbon nanotubes with different particle sizes on the surface of the steel fiber forms an embedding effect: small-size carbon nanotubes fill the micropores, the medium-size provides high surface energy binding force, and the large-size realizes rigid support, thus constructing a multi-scale reinforcement network. In terms of multi-scale reinforcement, the modified admixtures and carbon nanotube coatings work synergistically to improve the strength and toughness of the matrix from the nano, micron to macro levels. In terms of crack resistance, the steel fibers enhance the interface pull-out resistance through the coating, playing the role of bridging cracks; the modified admixtures provide pinning and blocking effects on the crack path, jointly limiting crack propagation. Overall, the synergistic effect of the modified admixtures and carbon nanotube-coated steel fibers significantly improves the density, interface bonding, crack resistance and durability of UHPC, and constructs a comprehensive reinforcement system from interface to matrix.
[0028] Furthermore, the lightweight filler is hollow glass microspheres or ceramsite powder.
[0029] Furthermore, the composite nano-reinforced material is nano-silicon dioxide, boron nitride nano-sheets and carbon nano-tubes, and the mass ratio is 4-5:1-2:2-3.
[0030] The nano-silicon dioxide particles in the composite nano-reinforced material of the present invention have a significant filling effect, which can fill the micropores of the matrix and improve the density; the boron nitride nanosheets provide excellent thermal conductivity, which can reduce the temperature gradient inside the matrix, thereby reducing crack propagation; the addition of carbon nanotubes forms a multi-scale reinforcement network in the matrix, further improving the toughness and crack resistance. The synergistic effect of the three nanomaterials significantly improves the overall mechanical properties of the UHPC material.
[0031] Furthermore, the high efficiency water reducer is a polycarboxylic acid high efficiency water reducer.
[0032] Furthermore, the nano-dispersant is a phosphate dispersant, a polycarboxylic acid dispersant or a non-ionic surfactant.
[0033] The fourth aspect of the present invention provides a method for preparing the above-mentioned ultra-high strength and lightweight UHPC material, comprising the following steps:
[0034] (1) Premixing of dry materials: weigh silicate cement, modified composite mineral admixture, quartz sand and lightweight filler in proportion and premix them in a mixer for 5-10 minutes;
[0035] (2) Dispersion of nano-reinforced materials: Mix the composite nano-reinforced materials with water, add a nano-dispersant, and disperse them using an ultrasonic device for 20-40 minutes to obtain a nano-reinforced slurry;
[0036] (3) Wet material mixing: add the dry material premixed in step (1) to the nano-enhanced slurry, stir, add a high-efficiency water reducer, and continue stirring for 10-20 minutes to obtain a mixture 1;
[0037] (4) steel fiber incorporation: strain-strengthened steel fibers are added to mixture 1, and a magnetic field oriented layout process is used to uniformly distribute the steel fibers to obtain mixture 2;
[0038] (5) Molding and curing: Mixture 2 is poured into a mold, allowed to stand for degassing and then cured for 20-30 hours, and then placed in a 90°C steam curing for 40-60 hours to complete curing and obtain an ultra-high strength and lightweight UHPC material.
[0039] The present invention balances the high strength and light weight requirements of UHPC through the optimized combination of modified composite mineral admixtures, lightweight fillers and composite nano-reinforced materials. The introduction of steel fibers significantly improves the toughness and crack resistance of the material. The ultrasonic dispersion process of nano-reinforced materials in the preparation process ensures the uniformity of dispersion and improves the material performance. The magnetic field oriented steel fiber layout technology ensures the uniform distribution of fibers in the matrix and the reinforcement effect.
[0040] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0041] The present invention provides a strain-strengthened steel fiber and ultra-high strength and lightweight UHPC material through composite material design and advanced preparation technology, which significantly improves the material performance and applicability. The strain-strengthened steel fiber has higher tensile strength, light weight and interface bonding force through Ti-Mg alloy core design, carbon nanotube composite coating and laser etching technology, which effectively overcomes the shortcomings of traditional steel fibers. The UHPC material formula uses silica fume, fly ash and metakaolin to compound and modify, which improves the strength, durability and adhesion of the matrix; nano-silicon dioxide, boron nitride nanosheets and carbon nanotubes work synergistically to optimize the interface transition zone, significantly enhancing the crack resistance and toughness of the matrix. At the same time, the introduction of lightweight fillers reduces the material density and meets the lightweight requirements. The preparation method of the present invention adopts ultrasonic dispersion technology and magnetic field directional layout technology to ensure the uniformity and efficient reinforcement effect of the material, and finally achieves a comprehensive balance of high performance and light weight, which is suitable for high-strength structures, bridge engineering and complex industrial environments. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Unless otherwise specified, the raw materials used in the examples are all common commercially available products. The following is an exemplary description:
[0044] Titanium powder was purchased from Baoji Yike Metal Materials Co., Ltd., with an average particle size of 45 μm and a purity of ≥99.5%;
[0045] Magnesium powder was purchased from Ningbo Quande Magnesium Industry Co., Ltd., with an average particle size of 50 μm and a purity of ≥99.8%;
[0046] Carbon nanotubes were purchased from Xi'an Qiyue Biotechnology Co., Ltd. in three sizes (small, medium, and large): diameter 5-10 nm, length 2-10 μm; diameter 10-30 nm, length 5-20 μm; diameter 30-50 nm, length 10-30 μm;
[0047] Polyvinyl alcohol was purchased from Shanghai Chemical Reagent Co., Ltd., PVA-1799;
[0048] Portland cement was purchased from China United Cement Group Co., Ltd., PO 42.5;
[0049] Silica fume was purchased from Henan Letao Silicon Material Technology Co., Ltd., with an average particle size of 0.1-0.2 μm;
[0050] Fly ash was purchased from Huaneng Power Co., Ltd., with an average particle size of 15-30 μm;
[0051] Metakaolin was purchased from Shandong Jinrunda Kaolin Technology Co., Ltd., with an average particle size of 5 μm;
[0052] Quartz sand was purchased from Jiangsu Minjiang Mining Co., Ltd., with an average particle size of 0.1-0.5 mm;
[0053] Hollow glass microspheres were purchased from Beijing Kailingda Inorganic Materials Co., Ltd., HG-25;
[0054] Nano-silica was purchased from Xi’an Qiyue Biotechnology Co., Ltd. with an average particle size of 50 nm;
[0055] Boron nitride nanosheets were purchased from Xi’an Qiyue Biotechnology Co., Ltd., Q-0303382;
[0056] Polycarboxylate water reducer was purchased from Shanghai Construction Materials Technology Group Co., Ltd., JH-03 polycarboxylate water reducer;
[0057] Sodium hexametaphosphate was purchased from Tianjin Chemical Reagent Research Institute, SP-85;
[0058] DAYE-UHPC steel fiber was purchased from Ganzhou Daye Metal Fiber Co., Ltd.;
[0059] Granulated blast furnace slag powder (GGBFS) was purchased from Jiangsu Subote New Materials Co., Ltd., S95 grade slag powder;
[0060] Limestone powder was purchased from Anhui Conch Cement Co., Ltd., with an average particle size of 8 μm;
[0061] Nano-alumina was purchased from Nanjing Xianfeng Nanomaterials Co., Ltd. with an average particle size of 20 nm;
[0062] Nano-titanium oxide was purchased from Hangzhou Wanjing New Materials Co., Ltd. with an average particle size of 20 nm;
[0063] Carbon black nanoparticles were purchased from Qingdao Detong Nanotechnology Co., Ltd. with an average particle size of 20 nm.
[0064] Example 1
[0065] This embodiment provides a method for preparing strain-hardened steel fibers, comprising the following steps:
[0066] (1) Preparation of core alloy
[0067] 85 parts by weight of titanium powder and 15 parts by weight of magnesium powder were weighed, and mixed for 30 minutes using a planetary mixer under argon protection to ensure uniform distribution of titanium powder and magnesium powder, and the mixed titanium-magnesium powder was placed in a vacuum melting furnace, evacuated to 0.02 Pa, and then high-purity argon (99.99%) was introduced to prevent oxidation; heated to 1600°C and kept warm for 1 hour to ensure that titanium and magnesium were fully melted to form a uniform Ti-Mg alloy liquid, and the molten Ti-Mg alloy liquid was drawn through a continuous drawing die, and a Ti-Mg alloy steel wire with a diameter of 100 μm was formed after cooling, and the drawing speed was controlled to 10 m / min. Deionized water was used as a cooling medium during the drawing process to avoid surface oxidation;
[0068] (2) Surface coating treatment
[0069] Small-particle carbon nanotubes with a diameter of 5-10 nm and a length of 2-10 μm, medium-particle carbon nanotubes with a diameter of 10-30 nm and a length of 5-20 μm, and large-particle carbon nanotubes with a diameter of 30-50 nm and a length of 10-30 μm were mixed in a mass ratio of 5:3:2 to obtain mixed carbon nanotubes, a polyvinyl alcohol (PVA) aqueous solution with a concentration of 8 wt% was prepared, 1.5 parts by weight of the mixed carbon nanotubes were weighed, and added to 10 parts by weight of the PVA aqueous solution, and the mixed solution was ultrasonically treated for 30 minutes using an ultrasonic dispersion device (power 400 W, frequency 40 kHz) to form a uniform and stable carbon nanotube-PVA suspension, and T The i-Mg alloy steel wire is immersed in the carbon nanotube-PVA suspension prepared above, and an ultrasonic-assisted dip coating process (power 300 W, frequency 35 kHz) is used to ensure that the carbon nanotubes are evenly coated on the surface of the alloy steel wire. The dip coating time is controlled to be 15 minutes. After the coating is completed, the alloy steel wire is taken out and placed in a vacuum drying oven and dried at 120° C. for 3 hours to ensure that the water in the PVA is completely evaporated and the coating is dense and uniform. The dried alloy steel wire is placed in a high-temperature furnace protected by argon gas, heated to 500° C., and kept warm for 1 hour to complete the thermal curing of the carbon nanotube-PVA composite layer to form a high-strength and dense composite coating to obtain a steel fiber;
[0070] (3) Surface laser etching
[0071] The steel fiber surface is treated by using a femtosecond laser etching device, the laser pulse width is set to 200fs, the frequency is 100kHz, the laser power is 2W, the laser scanning speed is set to 120mm / s, and the surface etching depth is controlled to 100nm through multiple scans to obtain the strain-strengthened steel fiber. A regular nanoscale concave-convex texture structure is formed on the surface of the steel fiber by laser etching, and the texture depth and distribution are uniform, thereby improving the interface bonding performance between the fiber and the matrix.
[0072] Example 2
[0073] This embodiment provides an ultra-high strength and lightweight UHPC material, which comprises the following components by weight: 45 parts of silicate cement, 25 parts of modified composite mineral admixture, 20 parts of quartz sand, 10 parts of lightweight filler (hollow glass microspheres), 5 parts of composite nano-reinforced material, 1.2 parts of high-efficiency water reducer (JH-03 type polycarboxylate water reducer), 0.6 parts of nano-dispersant (sodium hexametaphosphate), 1.3 parts of strain-strengthened steel fiber, and 13 parts of water;
[0074] The preparation method of the modified composite mineral admixture comprises the following steps:
[0075] (i) mixing silica fume, fly ash and metakaolin in a mass ratio of 5:2.5:2.8 to obtain a composite mineral admixture;
[0076] (ii) spraying a 4wt% aqueous solution of a silane coupling agent (KH-550) into the composite mineral admixture, wherein the mass of the silane coupling agent is 0.8% of the composite mineral admixture, and drying the admixture at 60°C for 30 minutes after the spraying is completed; then continuing to spray an 8wt% aqueous solution of sodium metasilicate, wherein the mass of the sodium metasilicate is 1.5% of the composite mineral admixture, and drying the admixture at 80°C for 2 hours after the spraying is completed; then continuing to spray a 3.5wt% aqueous solution of zirconium phosphate, wherein the mass of the zirconium phosphate is 0.8% of the composite mineral admixture, and drying the admixture at 100°C for 2 hours after the spraying is completed, and then roasting the admixture in a high-temperature furnace at 500°C for 1 hour to obtain a modified admixture;
[0077] (iii) Using air flow milling equipment to grind the modified admixture to control the particle size D50≤5 μm, thus obtaining the modified composite mineral admixture.
[0078] The composite nano-reinforced material is nano-silicon dioxide, boron nitride nano-sheets and carbon nano-tubes, with a mass ratio of 5:1.5:2.6;
[0079] The strain-hardened steel fiber is prepared by the method of Example 1.
[0080] The preparation method of the above-mentioned ultra-high strength and lightweight UHPC material comprises the following steps:
[0081] (1) Dry material premixing: Portland cement, modified composite mineral admixture, quartz sand and lightweight filler are weighed in proportion and premixed in a mixer for 7 minutes to ensure that all components are evenly mixed to form a uniform dry powder mixture;
[0082] (2) Dispersion of nano-reinforced materials: The composite nano-reinforced materials were mixed with water and stirred for 1 minute to form an initial mixed solution, a nano-dispersant was added, and the mixture was stirred with a magnetic stirrer for 5 minutes. The mixed solution was then treated with an ultrasonic dispersion device (power 400 W, frequency 40 kHz) for 30 minutes to ensure that the nano-reinforced materials were fully dispersed to form a uniform and stable nano-reinforced slurry;
[0083] (3) Wet material mixing: add the dry material premixed in step (1) to the nano-enhanced slurry, stir for 5 minutes to allow the dry material and slurry to initially blend, add a high-efficiency water reducer, and continue stirring for 15 minutes to obtain a mixture 1;
[0084] (4) Steel fiber incorporation: strain-strengthened steel fibers were added to mixture 1, and a magnetic field orientation layout process (magnetic field intensity 100 mT) was used to make the steel fibers form a uniform orientation distribution in the matrix, thereby obtaining mixture 2;
[0085] (5) Molding and curing: Mixture 2 was poured into a mold, allowed to stand for degassing and cured for 25 hours, and then placed in a 90°C steam curing box for 48 hours to complete curing and obtain an ultra-high strength and lightweight UHPC material.
[0086] Example 3
[0087] This embodiment provides an ultra-high strength and lightweight UHPC material, which comprises the following components by weight: 45 parts of silicate cement, 20 parts of modified composite mineral admixture, 25 parts of quartz sand, 13 parts of lightweight filler (hollow glass microspheres), 4 parts of composite nano-reinforced material, 1.2 parts of high-efficiency water reducer (JH-03 type polycarboxylate water reducer), 0.5 parts of nano-dispersant (sodium hexametaphosphate), 1.5 parts of strain-strengthened steel fiber, and 13 parts of water;
[0088] The mass ratio of silica fume, fly ash and metakaolin in the modified composite mineral admixture is 4:2.5:2.8, and the preparation method of the modified composite mineral admixture is the same as that in Example 2;
[0089] The composite nano-reinforced material is nano-silicon dioxide, boron nitride nano-sheets and carbon nano-tubes, with a mass ratio of 5:2:2.2;
[0090] The strain-hardened steel fiber is prepared by the method of Example 1.
[0091] The preparation method of the ultra-high strength and lightweight UHPC material is the same as that in Example 2.
[0092] Comparative Example 1
[0093] This comparative example provides an ultra-high strength and lightweight UHPC material, which differs from Example 2 in that the strain-strengthened steel fibers are replaced with commercially available steel fibers (DAYE-UHPC steel fibers).
[0094] Comparative Example 2
[0095] This comparative example provides an ultra-high strength and lightweight UHPC material, which differs from Example 2 in that carbon nanotubes of a single particle size with a diameter of 10-30 nm and a length of 5-20 μm are used in the preparation of strain-strengthened steel fibers, and the rest is the same as Example 2.
[0096] Comparative Example 3
[0097] This comparative example provides an ultra-high strength and lightweight UHPC material, which differs from Example 2 in that the modified composite mineral admixture is replaced by a mixture of granulated blast furnace slag powder (GGBFS), silica fume and limestone powder in a mass ratio of 5:2.5:2.8.
[0098] Comparative Example 4
[0099] This comparative example provides an ultra-high strength and lightweight UHPC material, which is different from Example 2 in that the composite mineral admixture is not modified.
[0100] Comparative Example 5
[0101] This comparative example provides an ultra-high strength and lightweight UHPC material, which is different from Example 2 in that the composite nano-reinforced material is nano-alumina, nano-titanium oxide and carbon black nanoparticles, with a mass ratio of 5:1.5:2.6.
[0102] Comparative Example 6
[0103] This comparative example provides an ultra-high strength and lightweight UHPC material, which is different from Example 2 in that the formula, measured by weight, comprises the following components: 45 parts of silicate cement, 15 parts of modified composite mineral admixture, 30 parts of quartz sand, 10 parts of lightweight filler (hollow glass microspheres), 10 parts of composite nano-reinforced material, 1.2 parts of high-efficiency water reducer (JH-03 type polycarboxylate water reducer), 0.6 parts of nano-dispersant (sodium hexametaphosphate), 3 parts of strain-strengthened steel fiber, and 15 parts of water.
[0104] Comparative Example 7
[0105] This comparative example provides an ultra-high strength and lightweight UHPC material, which is different from Example 2 in that the preparation method of the UHPC material includes the following steps:
[0106] (1) Mixing raw materials: Portland cement, modified composite mineral admixture, quartz sand, lightweight filler, composite nano-reinforced material, nano-dispersant and water were weighed in proportion, placed in a mixer and mixed for 20 minutes, and a high-efficiency water reducer was added, and stirring was continued for 15 minutes to obtain a mixture 1;
[0107] (2) Steel fiber incorporation: strain-strengthened steel fibers were added to mixture 1, and a magnetic field orientation process (magnetic field intensity of 100 mT) was used to allow the steel fibers to form a uniform orientation distribution in the matrix, thereby obtaining mixture 2;
[0108] (3) Molding and curing: Mixture 2 was poured into a mold, allowed to stand for degassing and cured for 25 hours, and then placed in a 90°C steam curing box for 48 hours to complete curing and obtain an ultra-high strength and lightweight UHPC material.
[0109] Performance Testing
[0110] The UHPC materials prepared in Examples 2-3 and Comparative Examples 1-7 were tested for performance. The tensile strength and compressive strength were tested according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete", the toughness index was tested according to ASTM C1609 / C1609M-19 "Fiber Reinforced Concrete Flexural Properties Test Method", and the density was tested according to GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method". The test results are shown in Table 1.
[0111] Table 1 Performance test results
[0112]
[0113]
[0114] It can be seen from the above performance test results that the UHPC materials prepared in Examples 1-2 have excellent mechanical strength and low density, and are characterized by ultra-high toughness and light weight. In Comparative Example 1, the strain-strengthened steel fibers are replaced with commercially available steel fibers. The commercially available steel fibers (DAYE-UHPC steel fibers) are made of low-carbon steel, have a smooth surface, and are not treated with a composite coating. The interfacial bonding force between the steel fibers and the matrix is weak, resulting in the steel fibers being unable to effectively prevent crack expansion, thereby reducing the overall compressive strength, tensile strength, and toughness of the material. At the same time, the density of DAYE-UHPC steel fibers is high, resulting in an increase in the density of the prepared UHPC material. In Comparative Example 2, carbon nanotubes of a single particle size are used in the preparation of strain-strengthened steel fibers, and a multi-scale reinforcement network cannot be formed. The filling and density of the coating are insufficient, and it is difficult to effectively cover the microscopic pores and textures on the surface of the steel fibers, resulting in a decrease in the uniformity of the coating and a weakening of the interfacial bonding force. In Comparative Example 3, the modified composite mineral admixture is replaced with a mixture of granulated blast furnace slag powder, silica fume and limestone powder. The blast furnace slag powder requires a long time for hydration activation, and its early reaction activity is low, and it cannot provide sufficient early strength. The limestone powder only plays a filling role and fails to significantly improve the matrix strength. The alternative admixture cannot effectively optimize the interface performance and mechanical strength of the matrix. In Comparative Example 4, the composite mineral admixture is not modified. When the composite mineral admixture is not modified, its surface activity is insufficient, and it is difficult to form a strong interface bond with other components in the matrix. The admixture has poor dispersibility and adsorption capacity in the matrix, and it is easy to produce agglomeration. The filling effect is limited, resulting in a decrease in matrix density and durability. In Comparative Example 5, the composite nano-reinforced material is replaced with nano-alumina, nano-titanium oxide and carbon black nanoparticles. The hydration promotion effect of nano-alumina and nano-titanium oxide is limited, and the carbon black particles are easy to agglomerate, and fail to effectively fill the matrix pores, resulting in a decrease in density, and then the compressive strength, tensile strength and toughness decrease. Comparative Example 6 changed the formula ratio, especially the modified composite mineral admixture was reduced, resulting in a decrease in the density and strength of the matrix, and the increase in quartz sand failed to make up for the lack of strength. Comparative Example 7 adjusted the preparation method, resulting in uneven mixing of raw materials and agglomeration of some materials, affecting the density and strength of the material.
[0115] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing strain-hardened steel fiber, comprising the following steps: (1) Preparation of core alloy 80-90 parts by weight of titanium powder and 10-20 parts by weight of magnesium powder are mixed, placed in a vacuum melting furnace, evacuated to 0.01-0.05 Pa, introduced with argon gas, heated to 1550-1650° C., and kept warm for 0.5-2 hours to obtain a Ti-Mg alloy, and then a Ti-Mg alloy steel wire is prepared by a continuous wire drawing process; (2) Surface coating treatment Mixing three carbon nanotubes with different particle sizes to obtain mixed carbon nanotubes, adding 1-2 parts by weight of the mixed carbon nanotubes to 10 parts by weight of a polyvinyl alcohol (PVA) aqueous solution with a concentration of 5-10wt% to obtain a suspension, immersing a Ti-Mg alloy steel wire in the suspension, coating the carbon nanotubes on the surface of the Ti-Mg alloy steel wire through ultrasonic treatment, and after coating, vacuum drying at 100-140° C. for 2-5 hours, and then placing in an argon environment at 450-550° C. for thermal curing for 0.5-2 hours to form a dense composite layer, thereby obtaining a steel fiber; (3) Surface laser etching The surface of the steel fiber is processed using a femtosecond laser etching device to obtain the strain-strengthened steel fiber.
2. The preparation method according to claim 1, characterized in that: The diameter of the Ti-Mg alloy steel wire in step (1) is 50-150 μm; the three carbon nanotubes with different particle sizes in step (2) are: small-particle carbon nanotubes with a diameter of 5-10 nm and a length of 2-10 μm, medium-particle carbon nanotubes with a diameter of 10-30 nm and a length of 5-20 μm, and large-particle carbon nanotubes with a diameter of 30-50 nm and a length of 10-30 μm, and the mass ratio of the small, medium and large carbon nanotubes with different particle sizes is (4-6): (2.5-3.5): (1.5-2.5).
3. The preparation method according to claim 1, characterized in that: The laser parameters in step (3) are set as follows: pulse width: 150-300 fs, frequency: 80-120 kHz, laser power: 1.5-3 W, scanning speed: 80-150 mm / s, etching depth: 50-300 nm.
4. A strain-strengthened steel fiber, characterized in that: The method is prepared by any one of claims 1 to 3.
5. An ultra-high strength and lightweight UHPC material, comprising the following components by weight: 40-50 parts of silicate cement, 20-30 parts of modified composite mineral admixture, 15-25 parts of quartz sand, 5-15 parts of lightweight filler, 3-6 parts of composite nano-reinforced material, 1-1.5 parts of high-efficiency water reducer, 0.3-0.7 parts of nano-dispersant, 0.8-1.7 parts of strain-strengthened steel fiber, and 10-15 parts of water; in, The strain-strengthened steel fiber is prepared by the method described in any one of claims 1 to 3; The preparation method of the modified composite mineral admixture comprises the following steps: (i) mixing silica fume, fly ash and metakaolin in a mass ratio of 4-5:2-3:2-3 to obtain a composite mineral admixture; (ii) spraying a silane coupling agent aqueous solution, a sodium metasilicate aqueous solution and a zirconium phosphate aqueous solution into the composite mineral admixture in sequence, drying the admixture after the spraying is completed, and then activating the admixture at 450-550° C. for 0.5-1.5 hours to obtain a modified admixture; (iii) The modified admixture is crushed to control the particle size D50≤5 μm, thereby obtaining the modified composite mineral admixture.
6. The ultra-high strength and lightweight UHPC material according to claim 5, characterized in that: The mass of the silane coupling agent is 0.5-1% of the composite mineral admixture, the mass of the sodium metasilicate is 1-2% of the composite mineral admixture, and the mass of the zirconium phosphate is 0.5-1% of the composite mineral admixture.
7. The ultra-high strength and lightweight UHPC material according to claim 5, characterized in that: The light filler is hollow glass microbeads or ceramsite powder.
8. The ultra-high strength and lightweight UHPC material according to claim 5, characterized in that: The composite nano-reinforced material is nano-silicon dioxide, boron nitride nano-sheets and carbon nano-tubes, and the mass ratio is 4-5:1-2:2-3.
9. The ultra-high strength and lightweight UHPC material according to claim 5, characterized in that: The high-efficiency water reducer is a polycarboxylic acid-based high-efficiency water reducer, and the nano-dispersant is a phosphate dispersant, a polycarboxylic acid dispersant or a non-ionic surfactant.
10. The method for preparing the ultra-high strength and lightweight UHPC material according to any one of claims 5 to 9, comprising the following steps: (1) Premixing of dry materials: weigh silicate cement, modified composite mineral admixture, quartz sand and lightweight filler in proportion and premix them in a mixer for 5-10 minutes; (2) Dispersion of nano-reinforced materials: Mix the composite nano-reinforced materials with water, add a nano-dispersant, and disperse them using an ultrasonic device for 20-40 minutes to obtain a nano-reinforced slurry; (3) Wet material mixing: add the dry material premixed in step (1) to the nano-enhanced slurry, stir, add a high-efficiency water reducer, and continue stirring for 10-20 minutes to obtain a mixture 1; (4) steel fiber incorporation: strain-strengthened steel fibers are added to mixture 1, and a magnetic field oriented layout process is used to uniformly distribute the steel fibers to obtain mixture 2; (5) Molding and curing: Mixture 2 is poured into a mold, allowed to stand for degassing and then cured for 20-30 hours, and then placed in a 90°C steam curing for 40-60 hours to complete curing and obtain an ultra-high strength and lightweight UHPC material.
Citation Information
Cited By
High-crack-resistance long-service-life concrete product and preparation method thereof
CN120157428A